Power system stabilization based on artificial intelligent techniques: a review - Hassan, L.H.; Moghavvemi, M.; Mohamed, H.A.F. (2009)
This paper reviews new approaches in modern research using Artificial Intelligent (AI) techniques to develop power system stabilizer (PSS). These techniques are Artificial Neural Network (ANN), fuzzy logic, hybrid artificial intelligent, expert systems, and optimization techniques base AI such as Genetic Algorithm (GA), Particle Swarm Optimization (PSO), Tabu Search (TS) algorithm, etc. Research showed controllers designed based on a conventional control theory, modern and adaptive control theories, suffer from some limitations. However, AI techniques proved to be able to overcome theses limits. Hence, more researchers preferred to utilize these approaches for the power systems. The review efforts geared towards PSS and excitation system stabilizer developed based on AI techniques, which effectively enhance both small signal stability and transient stability and equally provide superior performances. In addition, the dynamic performance of different AI based stabilizers are established and compared with other types of PSSs.